Investigating The Role of Marketing Content and Brand Image on Purchasing Decisions Mediated by Purchase Interest in Shop Online Users - Prayuda, Rafie (UJoST- Universal Journal of Science and Technology, 2024)
This research examines the variables of marketing content, brand image and purchasing decisions and is mediated by purchasing interest. The digital era is currently developing rapidly. The increase in digital transactions has also made consumers shift to online purchases, in this case e-commerce. The existence of interesting marketing content makes consumers interested in buying and also well-known brands make consumers not hesitate to buy. This research examines the variables of marketing content, brand image and purchasing decisions and is mediated by purchasing interest. Data sourced from 345 respondents was collected using a Google Form questionnaire. Data analysis using the SEM smartPLS 3.0 application. The results of this research are that marketing content has an influence on interest and purchasing interest has an influence on purchasing decisions, while brand image does not influence purchasing decisions. Purchase interest does not mediate the influence of marketing content on purchasing decisions.